2008
DOI: 10.1021/ct800242n
|View full text |Cite
|
Sign up to set email alerts
|

Fragment-Localized Kohn−Sham Orbitals via a Singles Configuration-Interaction Procedure and Application to Local Properties and Intermolecular Energy Decomposition Analysis

Abstract: Abstract:As for generating localized Hartree-Fock orbitals, we propose a potentially linearscaling singles-CI scheme to construct fragment-localized density functional theory (DFT) orbitals for molecular systems as water clusters. Due to the use of a deformation step instead of a localization step, the influence of the environment on each separate molecule can be studied in detail. The generated orbital set for the whole molecular system is strictly equivalent to a set of canonical orbitals and is a subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 63 publications
0
41
0
Order By: Relevance
“…While our results have been obtained at the Hartree-Fock level, recent studies clearly show that correlation acts on induction and leads to greater charge transfer energy 17, 40. For this reason, we computed the induction energies on selected water clusters at both HF and DFT level using a recently introduced energy decomposition analysis (EDA) technique based on single configuration-interaction (CI) localized fragment orbitals 65. We indeed find that the CT contribution increases slightly with DFT, however, overall it accounts for less than 20% of the total induction energy for monoligated complexes and presumably would be even less in the bulk water environment.…”
Section: Resultsmentioning
confidence: 99%
“…While our results have been obtained at the Hartree-Fock level, recent studies clearly show that correlation acts on induction and leads to greater charge transfer energy 17, 40. For this reason, we computed the induction energies on selected water clusters at both HF and DFT level using a recently introduced energy decomposition analysis (EDA) technique based on single configuration-interaction (CI) localized fragment orbitals 65. We indeed find that the CT contribution increases slightly with DFT, however, overall it accounts for less than 20% of the total induction energy for monoligated complexes and presumably would be even less in the bulk water environment.…”
Section: Resultsmentioning
confidence: 99%
“…Its inclusion in the total SIBFA interaction energy enabled to restore the Td versus SP preference consistent with the QC computations. Future works will deal with (1) the inclusion of correlation effects with our many-body formalism through density functional theory [26,37] or post-HF methods [7] ; (2) alternative formulations based on density overlap. [1,15] …”
Section: Discussionmentioning
confidence: 99%
“…It must be recalled, on the other hand that in the present computations, the wave functions of the frozen monomers used to construct the final dimer wave functions within the RVS procedure are computed using the monomer-centered basis elements. It was shown that the use of the dimer basis for each monomer could affect the final values of exchange-repulsion [26] acting as a ' 'basis set superposition error"-like effect on exchange-repulsion, which also modifies the Coulomb contribution. By construction, the present RVS computations are monomer-centered consistent with the fact that all PMM methods resort to QC-derived properties of the isolated fragments to compute intermolecular interactions, namely multipoles and polarizabilities.…”
Section: Influence Of the Basis Set And Of The Pseudo-potential On E mentioning
confidence: 99%
“…Our formalism may also be useful when interpreting different interaction energy decomposition schemes that have recently been proposed within the DFT approach [12][13][14]36].…”
Section: Discussionmentioning
confidence: 99%
“…Approximate DFT treatments have already been advanced by Cortona and coworkers [10,11]; see also recent energy decomposition schemes proposed in Refs. [12][13][14], and Refs. therein, as well as the density functional formulation of SAPT [15,16].…”
Section: Introductionmentioning
confidence: 99%